1997
DOI: 10.1086/301646
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Mutations in the RPGR Gene That Are Identified in 20% of Families with X-Linked Retinitis Pigmentosa

Abstract: The RPGR (retinitis pigmentosa GTPase regulator) gene for RP3, the most frequent genetic subtype of X-linked retinitis pigmentosa (XLRP), has been shown to be mutated in 10%-15% of European XLRP patients. We have examined the RPGR gene for mutations in a cohort of 80 affected males from apparently unrelated XLRP families, by direct sequencing of the PCR-amplified products from the genomic DNA. Fifteen different putative disease-causing mutations were identified in 17 of the 80 families; these include four nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 13 publications
3
57
0
Order By: Relevance
“…This consequence is a protein with a small 'charged domain'. 12 These three mutations were absent in 70 XLRP and 120 control chromosomes, indicating that they are not simply frequent variant alleles in these populations.…”
Section: Novel Mutations In Rpgr Gene Mg Miano Et Al Tmentioning
confidence: 92%
See 2 more Smart Citations
“…This consequence is a protein with a small 'charged domain'. 12 These three mutations were absent in 70 XLRP and 120 control chromosomes, indicating that they are not simply frequent variant alleles in these populations.…”
Section: Novel Mutations In Rpgr Gene Mg Miano Et Al Tmentioning
confidence: 92%
“…12 Most mutations fall in exons encoding RCC1 repeats, the characteristic domain of the amino-terminal region of RPGR putative protein. It is conceivable that RPGR is not responsible for most cases of XLRP linked to this region and that another RP novel gene(s) remains unidentified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the latter is the X-linked locus RP3 (OMIM 312610), which accounts for the majority of X-linked RP families by linkage studies. The retinal disease associated with RP3 appears to have an early age of onset (1) and exhibits early involvement of both cones and rods (2)(3)(4)(5)(6)(7). This is in contrast with other types of RP in which rods are primarily affected followed by a secondary degeneration of cones.…”
Section: R Etinitis Pigmentosa (Rp) Is a Group Of Hereditary Retinalmentioning
confidence: 99%
“…The two major loci, RP2 on Xp11.23 [MIM# 312600, Thiselton et al, 1996] and RP3 on Xp21.1 [MIM# 312610, Musarella et al, 1990] account for 20-25% and 70% of cases, respectively [Teague et al, 1994;Ott et al, 1990]. Although the disease genes from both genetic intervals have been isolated [RP2 by Schwahn et al, 1998 and RPGR by Meindl et al, 1996;Roepman et al, 1996], XLRP cases linked to the RP3 locus have perplexed investigators in the past, since only 20% of patients had mutations identified in the RPGR gene [Buraczynska et al, 1997;Miano et al, 1999;Zito et al, 1999;Sharon et al, 2000]. This raised the suspicion that some mutational hot spots remained to be identified and in 2000, Vervoort et al described a new RPGR exon, called ORF15, in which they identified mutations in 60% of XLRP patients .…”
Section: Introductionmentioning
confidence: 99%